Evolutionary Perspectives on Myrmecophily in Ladybirds - Amélie Vantaux; Olivier Roux; Alexandra Magro; Jérôme Orivel (Psyche: A Journal of Entomology)
Myrmecophiles are species that usually have developed specialized traits to cope with the aggressiveness of ants enabling them to live in their vicinity. Many coccinellid species are predators of Hemiptera; the latter is also often protected by ants. Therefore these ladybirds frequently interact with ants, and some species have become myrmecophilous. In this paper, we aim to provide an overview of the evolution of myrmecophilous traits in ladybirds. We then discuss the costs and benefits of myrmecophily and the dietary shift to myrmecophagy observed in a few species.